Individuals Family History Positive for Alcoholism Show fMRI Differences in Reward Sensitivity that are Related to Impulsivity Factors - Andrews, Melissa M. (2010)
BACKGROUND: Substance abusing individuals tend to display abnormal reward processing and a vulnerability to being impulsive. Detoxified alcoholics show differences in regional brain activation during a monetary incentive delay (MID) task. However there is limited information on whether this uncharacteristic behavior represents a biological predisposition towards alcohol abuse, a consequence of chronic alcohol use, or both. METHODS: We investigated proposed neural correlates of substance disorder risk by examining reward system activity during a MID task with separate reward prospect, reward anticipation, and reward outcome phases in 30 individuals with and 19 without family histories of alcoholism. All subjects were healthy, lacked DSM-IV past or current alcohol or substance abuse histories, and were free of illegal substances as verified by a urine toxicology screening at the time of scanning. Additionally, we explored specific correlations between task-related nucleus accumbens (NAcc) activation and distinct factor analysis-derived domains of behavioral impulsivity. RESULTS: During reward anticipation, fMRI data confirmed blunted NAcc activation in family history positive subjects. In addition, we found atypical activation in additional reward-associated brain regions during additional task phases. We further found a significant negative correlation between NAcc activation during reward anticipation and an impulsivity construct. CONCLUSIONS: Overall, results demonstrate that sensitivity of the reward circuit, including NAcc, is functionally different in alcoholism FHP individuals in multiple regards.